Long-term Outcome of Severe Preeclampsia Cases: Cross – Sectional Study: Keluaran Jangka Panjang Kasus Preeklamsia Berat: Studi Potong Lintang - Yuditiya Purwosunu; Nurida M. Siagian (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objectives: To investigate the long term outcome of severe preeclampsia mother by clinically and laboratory, and the long term outcome of the baby that she delivered. Method: This is a cross sectional study was conducted at Obstetrics Outpatient Clinic Dr. Cipto Mangunkusumo General Hospital (Cipto Mangunkusumo NCGH) on January–June 2017, of patients with previous severe preeclampsia that gave birth in Cipto Mangunkusumo NCGHon January 2014 – December 2016, and was descriptively analyze using SPSS Statistics 24. Results: One hundred and twenty seven patients were studied, divided into 3 groups of post – delivery time which were 6 months, 12 months, and 24 months. The 6 months’ group, mean of blood pressure were 147/92 mmHg (SD 38/SD 39), BMI 29 kg/m2 (SD 6), CRP level 16.6 mg/l (0.3 – 42.60) and urine protein dipstick 1 (0 – 3). The 12 months’ group, mean of blood pressure were 112/88 mmHg (SD 12/SD 24), BMI 21s kg/m2 (SD 7), CRP level 12.7 mg/l (3.4 – 15.2) and urine protein dipstick 0 (0 – 3). The 24 months’ group, mean blood pressure 154/95 mmHg (SD 45/SD 62), BMI 28.83 kg/m2, CRP level 14,2 mg/l (SD 8.54) and urine protein dipstick 0 (0 – 3). Meanwhile, the long – term outcome of babies that 68% baby were born with preterm condition and mean birth weight were 1943 grams (SD 1245), the 5th minute Apgar score >7 were 63.78%, and only 44.88% baby had normal growth development. Conclusion: The long – term outcome patients with previous severe preeclampsia are blood pressure, BMI, and CRP level still high, and negative urine protein level until 2 years of post – delivery. The long – term outcome of the babies that delivered were on preterm condition and low birth weight, with less than 50% had normal growth and development. Keywords: c–reactive protein, growth and development, proteinuria, post–delivery, severe preeclampsia. Abstrak Tujuan: Untuk mengetahui keluaran jangka panjang pada pasien ibu PEB dari sudut klinis dan laboratoris, serta keluaran jangka panjang bayi yang dilahirkan. Metode: Penelitian ini menggunakan desain potong lintang terhadap pasien riwayat PEB yang pernah melahirkan di RSUPN Dr. Cipto Mangunkusumo pada bulan Januari 2014–Desember 2016. Subjek diminta datang ke Poli Obstetri RSUPN Dr. Cipto Mangunkusumo pada Januari–Juni 2017 untuk dilakukan pemeriksaan klinis dan laboratoris (CRP dan protein urin), serta dilakukan analisa deskriptif menggunakan SPSS Statistik 24. Hasil: Sebanyak 127 pasien yang diteliti terbagi dalam 3 kelompok yaitu pasien riwayat PEB pasca persalinan 6 bulan (kelompok I), 12 bulan (kelompok II), dan 24 bulan (kelompok III). Kelompok I didapatkan rerata tekanan darah (TD) 147/92 mmHg (SD 38/SD 39), IMT 29 kg/m2 (SD 6), kadar CRP 16,6 mg/l (0,3 – 42,60) dan protein urin 1 (0 – 3). Kelompok II didapatkan rerata tekanan darah (TD) 112/88 mmHg (SD 12/SD 24), IMT 21 kg/m2 (SD 7), kadar CRP 12,7 mg/l (3,4 – 15,2) dan protein urin 0 (0 – 3). Kelompok III rerata TD 154/95 mmHg (SD 45/SD 62), IMT 28,83 kg/m2, dengan rerata kadar CRP 14,2 mg/l (SD 8,54) dan protein urin 0 (0 – 3). Sedangkan keluaran jangka panjang bayi yang dilahirkan bahwa 68% lahir dengan kondisi preterm dengan rerata berat lahir 1.943 gram (SD 1.245), nilai Apgar menit ke-5 >7 63,78%, dan hanya 44,88% tumbuh – kembang bayi normal. Kesimpulan: Gambaran keluaran jangka panjang pasien riwayat PEB didapatkan tekanan darah, IMT dan kadar CRP masih tinggi, serta protein urin urin negatif setelah 2 tahun pascapersalinan. Keluaran jangka panjang bayi yang dilahirkan mayoritas kondisi preterm dan berat lahir rendah, dengan kurang dari 50% bayi tumbuh – kembang normal. Kata kunci: c– reactive protein, preeklamsia berat, proteinuria, pascapersalinan, tumbuh kembang bayi.